Detection of edible bird’s nest using Fourier Transform Infrared Spectroscopy (FTIR) combined with Principle Component Analysis (PCA) - S, Noor Atikah; Tukiran, Nur Azira; Mohd Ali, Nurul Azarima; Ghazali, Haizatul Hadirah; Zulkifli, Siti Nur Syahirah (HH Publisher, 2020)
Edible bird’s nest (EBN) is rich in nutrients and health benefits; making it one of the Chinese delicacies over the centuries. However, due to the overpriced and limited supply of EBN, it is being adulterated with other cheaper versions. Therefore, the aim of this study is to establish a method of detecting adulterants in EBN using Fourier transform infrared spectroscopy (FTIR) as the spectrum fingerprinting analysis together with principal component analysis (PCA). Spiked samples have been developed for Tremella fungus and porcine gelatine at the concentrations of 1%, 5%, 10%, 20% and 30% (w/w). The FTIR method combined with PCA analysis was able to detect the adulteration of porcine gelatine and Tremella fungus in the sample of adulterated EBNs at low concentration of 1% (w/w). The simple approach employing FTIR combined with PCA may provide a useful tool for EBN detection.